Environmental Design, Personality, and Online Learning. (September 2018) - Stone, Nancy J.
Students completed an online tutorial presented as a video or PowerPoint presentation in a room with or without a window with blue, green, red, or white draperies to determine the impact of the environment on online learning. Students' scores improved significantly from pretest to posttest; however, contrary to expectation, there were no main effects of windows, color, or the type of tutorial. There was a Room X Color interaction effect. Contrary to expectation, posttest scores were highest in the windowed room with red drapes and in the windowless room with green or white drapes. The lowest posttest scores occurred in a windowless room with red drapes and a windowed room with green drapes. Learners high in extraversion and agreeableness tended to have lower posttest scores, but high levels of conscientiousness were not related to performance. These results suggest that the presence of a window influences the impact of color in the learning environment, but the relation between personality and online performance is still unclear.